Clinical efficacy of efgartigimod combined with intravenous methylprednisolone in the acute phase of neuromyelitis optica spectrum disorders - Wenjing Yang; Pei Chen; Jiaxuan Guo; Huiyu Feng; Xin Huang (Orphanet Journal of Rare Diseases)
Abstract Background Neuromyelitis Optica Spectrum Disorders (NMOSD) comprise a group of autoimmune-mediated, inflammatory, demyelinating central nervous system diseases caused by aquaporin-4 (AQP4) IgG autoantibodies. Efgartigimod is a human IgG Fc fragment that reduces antibody titers by targeting the neonatal Fc receptor (FcRn). This study documents the efficacy of efgartigimod combined with intravenous methylprednisolone (IVMP) in the acute phase of NMOSD. Methods In this retrospective study, the medical records of NMOSD patients with acute attack who received efgartigimod plus IVMP or IVMP were reviewed. Treatment efficacy was assessed by the Expanded Disability Scale Score (EDSS) before and one month after treatment. Any side effects that occurred during the treatment period were recorded. Results This study was performed on 11 patients (efgartigimod plus IVMP group [n = 4] and IVMP group [n = 7]). Efgartigimod plus IVMP was effective and had a satisfactory safety profile. EDSS was reduced by 0.5 ± 0.32 compared with the IVMP group (0.27 ± 0.02). Immunoglobulin was decreased in three patients, and the immunoglobulin G (IgG) levels gradually increased approximately 8 weeks after the last administration. Hyperlipidemia and elevated white blood cell count were common side effects. No infections or deaths occurred. Conclusions Efgartigimod plus IVMP treatment is safe and well-tolerated in patients with acute-phase NMOSD.